Understanding of MSME Owners in Sidoarjo Regency in The Preparation of Financial Statements Based on SAK EMKM - Rahayu, Duwi; Hanif, Aisha; Shifa Chofifah, Geulis (Universitas Muhammadiyah Malang, 2024)
Purpose: This study examines the effect of education level, educational background, business age, business scale, and information and socialization on the understanding of Micro, Small and Medium Enterprises (MSMEs) actors in preparing financial statements based on the Indonesian Financial Accounting Standards (SAK) for EMKM. This study focuses on MSMEs that are members of the Sidoarjo Food and Beverage Association (ASMAMINDA) in Sidoarjo Regency. Methodology/approach: This research uses quantitative research methods. The data used in this study are primary data collected through distributing questionnaires directly to respondents. The population in this study were 60 participants consisting of administrators and members of ASMAMINDA UMKM. The sampling technique used in this study was saturated sampling. The data analysis technique used in this research is multiple linear analysis. Findings: The findings of this study indicate that the level of education does not affect the understanding of SAK EMKM. Likewise, educational background does not affect the understanding of SAK EMKM, as well as business age. However, business scale has a significant effect on the understanding of SAK EMKM. In addition, the provision of information and socialization has a significant impact on the understanding of SAK EMKM. Practical Implications : This research provides practical implications for MSMEs to increase understanding of SAK EMKM as the responsibility of MSME actors in preparing financial reports. Originality/ Value : This study analyzes the effect of education level, educational background, business age, business scale, and information and socialization on the understanding of Micro, Small and Medium Enterprises (MSMEs) incorporated in the Sidoarjo Food and Beverage Association (ASMAMINDA).